Konsep Hijrah dalam Al-Tafsir Al-Munir - Zuhairi, Faris; Sulthoni, Akhmad; Romadlon, Arif Firdausi Nur (Adh Dhiya | Journal of The Quran and Tafseer Studies, 2024)
In the phenomenon of hijrah among public figures via social media, this action attracts attention and has an impact on appearance and consumer behavior. Hijrah is considered an act of faith that reflects indifference to the world in order to achieve piety. The event of the Hijrah of the Prophet Muhammad. and the meaning of the word "hijrah" in the Koran is the focus of research. Using library research methods and referring to the book Al Munir by Wahbah Az-Zuhaili, this research analyzes the interpretation of the hijrah and its implementation in everyday life. The results of the analysis show that hijrah, in the context of the verses of the Qur'an, involves changes in attitudes and behavior to get closer to Allah. Certain verses, such as Al-Baqarah (2:218), An-Nisa' (4:97-100), Al-Anfal (8:72-75), An-Nahl (16:41), Maryam (19 :49), Al-Ankabut (29:26,56), Ash-Shofat (37:99), Az-Zumar (39:10), Ad-Dukhan (44:21), Adz-Dzariyat (51:50) , Al-Hasyr (59:8), Al-Mumlahanah (60:10), Al-Muzzammil (73:19), and Al-Muddatstsir (74:5), emphasize the importance of hijrah as Allah's command to maintain faith, personal safety , and fighting for religion. Hijrah also involves changes to avoid shirk, evil, and sinful acts, viewing it as an important step in the spiritual journey towards truth and a better life, with the Qur'an as a guide to life.